Apical Sealing Ability of Different Endodontic Sealers Using Glucose Penetration Test: A Standardized Methodological Approach - Nik Rozainah Nik Abdul Ghani; Tahir Yusuf Noorani; Aimi Kamarudin; Galvin Sim Siang Lin (Cumhuriyet University, 2020)
Objectives: To compare the apical sealing ability of four endodontic sealers based on glucose penetration method and validate the uses of contralateral teeth to provide a well-balanced experimental group. Materials and methods: One-hundred-and-twenty (sixty pair) extracted contralateral lower premolars were selected and undergone strict radiographic protocol. Root canal anatomy of each pair contralateral teeth was matched buccolingually and mesiodistally according to inclusion criteria (single canal, mature apical foramen, canal type, canal width, length, and curvature). Matched-pair contralateral teeth were then reevaluated using CBCT and divided into right and left sides (n=60, each side). Next, all canals were instrumented up to size 30, taper 0.06. Subsequently, teeth were subdivided into five groups for each side and obturated with single cone gutta-percha (GP) and various sealers: Group 1 - GP only (control); Group 2 - EndoRez; Group 3 - Sealapex; Group 4 - EndoSeal MTA and Group 5 - BioRoot RCS. All samples were placed in an incubator at 37°C, 100% humidity for 72 hours. Four matched-pair teeth from each group were then subjected to thermocycling for 100 cycles, 1000 cycles and 10000 cycles, respectively. After that, they were decoronated, coated with three layers of nail varnish, and used for glucose penetration test. The concentrations of glucose (mmol/L) were measured after 24 hours. Data analyzed using One-way ANOVA complemented by post hoc Dunnett T3 Test and Paired sample T-Test. Results: EndoSeal MTA demonstrated statistically significant (p<0.05) lowest glucose penetration followed by BioRoot RCS, Sealapex, EndoRez, and lastly control group. Apical sealing ability decreased as the number of thermocycles increased. No significant difference (p>0.05) was found between matched-pair contralateral teeth. Conclusions: Bioceramic sealers demonstrated better sealing ability than resin and calcium hydroxide sealers. Using matched-pair contralateral teeth provided a well-balanced experimental group.